CAUSATIVE BACTERIA AND ANTIBIOTIC RESISTANCE IN NEONATAL SEPSIS - Najeeb, Shahzad; Gillani, Saima; Ullah, Rifayyat; Rehman, Anees ur (Journal of Ayub Medical College Abbottabad, 2012)
Background: Neonatal sepsis is characterised by bacteraemia and clinical symptoms caused by microorganisms and their toxic products. Gram negative bacteria are the commonest causes of neonatal Sepsis. The resistance to the commonly used antibiotics is alarmingly high. The major reason for emerging resistance against antibiotics is that doctors often do not take blood cultures before starting antibiotics. We have carried out this study to find out various bacteria causing neonatal sepsis and their susceptibility to antibiotics for better management of neonatal sepsis. Methods: A total of 130 neonates with sepsis who were found to be blood culture positive were taken in this study. Culture/sensitivity was done, isolated organisms identified and their sensitivity/resistance was noted against different antibiotics. Data were arranged in terms of frequencies and percentage. Results: Out of 130 culture proven cases of neonatal sepsis, gram negative bacteria were found in 71 (54.6%) cases and gram positive bacteria in 59 (45.4%) cases. Staphylococcus aureus was the most common bacteria found in 35 (26.9%) cases followed by Escherichia coli in 30 (23.1%) cases. Acinetobacter species, Staphylococcus epidermidis, Klebseila, Streptococci, Enterobacter cloacae and Morexella species were found in 17 (13.1%), 17 (13.1%), 13 (10%), 7 (5.4%), 6 (4.6%), and 5 (3.8%) cases respectively. In most of the cases causative organisms were found to be resistant to commonly used antibiotics like ampicillin, amoxicillin, cefotaxime, and ceftriaxone (77.7%, 81.5%, 63.1%, and 66.9% respectively). There was comparatively less (56.9%) resistance to ceftazidime. Gentamicin had resistance in 55.1% cases, while amikacin and tobramycin had relatively less resistance (17.4% and 34.8% cases respectively). Quinolones and imipenem had relatively less resistance. Vancomycin was found to be effective in 100% cases of Staphylococcus group. Conclusion: Staphylococcus aureus are the most common gram positive bacteria and Escherichia coli are the most common gram negative bacteria causing neonatal sepsis. Resistance to commonly used antibiotics is alarmingly increasing. Continued surveillance is mandatory to assess the resistance pattern at a certain level. Keywords: Neonatal sepsis, bacterial isolates, Antibiotic susceptibility, Drug resistance, gram-positive, gram-negative